Building wellness performance and work engagement. Issue 4 (27th September 2022) - Ukai, Masanari; Chimoto, Yuto; Murakami, Takuya; Suzuki, Yuya; Tanabe, Shin‐ichi
Abstract: The aim of this study was to evaluate the effect of building wellness performance on the productivity of office workers. In six offices with different CASBEE Wellness Office (CASBEE‐WO) scores, a questionnaire survey on indoor environment satisfaction, work efficiency, CASBEE Office Health Checklist (CASBEE‐OHC) simplified version, and work engagement was conducted. The results revealed that most workers in offices with high wellness performance reported more satisfaction with the thermal, light, sound, and air quality environments. In addition, the overall indoor environment improved the work efficiency of workers. Moreover, workers in offices with high CASBEE‐WO scores tended to have high CASBEE‐OHC simplified version scores. In the offices with high CASBEE‐WO scores, the top 20% of workers with high work engagement tended to have higher CASBEE‐OHC simplified version scores than the remaining 80%. According to the "80/20 law, " most outcomes of a group depend on the top 20% of productive workers. Thus, considering the wellness performance of the office, it may be possible that the productivity of workers with high work engagement will be improved. Abstract : The aim of this study is to evaluate the effect of building wellness performance on the productivity of office workers. In the offices with high CASBEE‐WO scores, the top 20% of workers with high work engagement tended to have higher CASBEE‐OHC simplified version scores than the remaining 80%. According to the "80/20 law, " most outcomes of a group depend on the top 20% of productive workers. Thus, considering the wellness performance of the office, it may be possible that the productivity of workers with high work engagement will be improved.